COMPARISON OF HBA1C LEVELS AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS WITH AND WITHOUT CHRONIC COMPLICATIONS AT BALI ROYAL GENERAL HOSPITAL - Wulandari, Christina Nyoman; Atmaja, Kadek Surya; Masyeni, Sri Masyeni; Yudistira, Komang Aditya (JURNAL WIDYA MEDIKA, 2026)
Diabetes mellitus (DM) remains a major public health problem globally. Glycated hemoglobin (HbA1c) is widely used to assess long-term glycemic control in type 2 diabetes mellitus (T2DM), and persistent poor control may precipitate chronic microvascular and macrovascular complications. However, HbA1c profiles among hospitalized T2DM patients with established chronic complications in tertiary referral settings are still limited. This study compared HbA1c values between hospitalized T2DM patients with and without chronic complications at Bali Royal General Hospital. A cross-sectional analytic observational study was conducted using 130 inpatient T2DM medical records from 2022–2024 obtained through consecutive sampling. Descriptive variables included sex, age, antidiabetic regimen (oral vs injectable), and hypertension status. Chronic complications were categorized as macrovascular or microvascular based on clinical diagnoses documented in the medical records. Most patients were women (57.7%), with a mean age of 60.57 ± 10.41 years. Injectable therapy predominated (66.2%), and 58.5% had no documented hypertension. Patients with chronic complications had a higher median HbA1c than those without complications (8.60% [5.0–15.0] vs 7.50% [4.9–15.0]; p = 0.040). Overall, HbA1c levels were frequently above common treatment targets, indicating suboptimal long-term glycemic control in this inpatient cohort. Among hospitalized T2DM patients in a tertiary referral hospital, chronic complications were associated with significantly higher HbA1c levels, reflecting poorer long-term glycemic control. These findings highlight the need for sustained HbA1c optimization alongside comprehensive risk-factor management to mitigate long-term complication risk in referral settings.